“Alternative Selves” and Authority in the Fiction of Jane Urquhart - Filipczak, Dorota (The Woman Artist: Essays in memory of Dorota Filipczak, 2024)
The article engages with “alternative selves,” a concept found in The Stone Carvers by a Canadian writer, Jane Urquhart. Her fiction is first seen in the context of selected texts by Lucy Maud Montgomery, Margaret Laurence and Alice Munro, who explore the clash between female characters’ conventional roles and their “secret” selves. My analysis was inspired by Pamela Sue Anderson’s A Feminist Philosophy of Religion, which stresses the need for “reinventing ourselves as other” in the face of biased beliefs and dominant epistemology. In particular, my article refers to Anderson’s concern with Kant’s imaginary from The Critique of Pure Reason, where “the territory of pure understanding” is projected on the island, while desire, chaos and death are identified with the sea. Seen through the prism of a feminist reading of the philosophical imaginary, the sea becomes the female beyond. Urquhart’s three novels: Away, The Stone Carvers and A Map of Glass dissolve Kantian opposition between island and water, by showing how reason is invaded by desire and death, and how the female protagonist embodies the elements that have been repressed. The article ends with the analysis of a Homeric intertext in A Map of Glass, where Sylvia identifies with Odysseus “lashed to the mast” so that he would not respond to the call of the siren song. Reading Homer’s passage on the siren song, one realizes that the use of the Kantian imaginary turns Ithaca into the island of truth, and the sea into the stormy beyond, identified with desire, death and femaleness. While the Odyssey suppresses the dangerous message of the siren song, Urquhart’s fiction rewrites it and reclaims it as positive inspiration for the female protagonist.